Analysis of The Formation of Regional Apparatus Organizations in The City of Surakarta: Authority Perspective, Regional Vision and Mission, Regional Characteristics and Community Needs - Rohmadin, Sulthon (Universitas Sultan Ageng Tirtayasa, 2024)
The government's institutional arrangements are more focused on efforts to rightsize, namely efforts to simplify government bureaucracy, which are directed at developing organizations that are more proportional and transparent, so that these efforts are expected to ensure that regional apparatus organizations will not be too large in line with the spirit of renewal of government functions (reinventing government) in order to support the realization of good regional governance (good local government). To get there, regional government organizations in their formation must be in harmony with the authority, vision, mission, and characteristics of the region and society. This research uses a qualitative method with a case study approach. Primary data collection techniques include in-depth interviews and focus group discussion. From the analysis of the formation of regional government organizations in the City of Surakarta, it is clear that only part of the five propositions that form the basis of regional government organizational theory are used, namely the fourth proposition relating to community characteristics and the fifth proposition, which is closely related to information technology support. Meanwhile, the first (authority), second (regional vision and mission), and third (work area and jurisdiction) propositions are not used.